Large expansion of morphologically heterogeneous mammary epithelial cells, including the luminal phenotype, from human breast tumours - Krásná, L; Dudorkinová, D; Vedralová, J; Veselý, P; Pokorná, E; Kudlácková, I; Chaloupková, A; Petruzelka, L; Danes, J; Matousková, E (Breast cancer research and treatment, 2002)
Regular expansion of heterogeneous populations of epithelial cells, including the luminal phenotype, was achieved from small biopsies of human breast tumours and cutaneous metastases by optimized feeder layer technique based on irradiated NIH 3T3 cells. Forty-one out of 47 primary tumour specimens and all three cutaneous metastases grew successfully for two to 10 passages in vitro. The main phenotypes of cultured cells and their changes in subcultures were characterized using immunocytochemistry and phase contrast microscopy (in few cases also time-lapse recording). In the majority of cultured cell populations a fraction of cells positive for keratin 19 (K19+), typical for the luminal phenotype, was detected. This is the cell type from which breast carcinoma is supposed to arise. While in cultures derived from benign lesions only basic phenotypes of luminal and myoepithelial cells were found, in cultures derived from malignant tumours unusual phenotypes of epithelial cells, in their majority K19+, were detected. The growth properties of cells from six benign and seven malignant samples were analyzed in detail. In the analyzed cell populations the culture lifetime - related to the number of colony-forming cells varied for cells from malignant tumours between 21 and 51 and from benign tumours between 22 and 40 cell generations. The total number of passages achieved was three to seven for malignant or four to nine for benign cultures. In spite of negative results of tumourigenicity testing in immunologically compromised Nu/nu mice the potential to culture apparently neoplastic cells was indicated by positive immunostaining for the p53 oncoprotein (seven of 23 tested malignant cases), the src oncoprotein (five of eight), and overexpression of the c-erbB-2 protein (five of 26). This was further confirmed by successful cultivation of malignant cells from cutaneous metastases. Two of the three metastasis-derived cultures were nearly homogeneously positive for K19 while the third was almost negative. The results proved the optimized feeder layer technique to be useful for regular yielding of large amounts of epithelial cells from small tumour biopsies and for supporting the majority of cell phenotypes present in the original tumour. Therefore, it appeared to be a promising tool for further analysis of interactions between luminal and myoepithelial cells in the development of human breast carcinoma and for the study of individual tumours.
Keywords: kokultivační techniky; dospělí; Animals; Cell Count; nádory prsu; 3T3 Cells; Female; Phenotype; Keratins; Adult; ženské pohlaví; Microscopy, Phase-Contrast; Immunohistochemistry; lidé; Breast; Mice; Carcinoma, Ductal, Breast; keratiny; prsy; Breast Neoplasms; studie případů a kontrol; nádorové buňky kultivované; kultivované buňky; myši; imunohistochemie; nádory kůže; Cell Transformation, Neoplastic; Cells, Cultured; Tumor Cells, Cultured; Case-Control Studies; Aged; Skin Neoplasms; Coculture Techniques; buňky 3T3; počet buněk; nádorová transformace buněk; lidé středního věku; senioři; zvířata; duktální karcinom prsu; fenotyp; Middle Aged; mikroskopie fázově kontrastní; Humans